USM CHEMISTRY PROGRAMME RECEIVES INTERNATIONAL ACCREDITATION FROM THE ROYAL SOCIETY OF CHEMISTRY (RSC) UK - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 22 February 2016 The Bachelor of Science degree in Chemistry offered by the School of Chemical Sciences, Universiti Sains Malaysia (USM) has received international recognition recently when it was accredited by the Royal Society of Chemistry (RSC), United Kingdom.